Power‐assisted rotary cutter with negative pressure suction through small incision for axillary osmidrosis. Issue 8 (15th June 2022) - Zhang, Jianfei; Han, Pengpeng; Yang, Feng; Jiang, Bin; Tang, Yujun; Xiao, Xia
Abstract: Background: The glandular fluid secreted by apocrine sweat glands is decomposed by parasitic bacteria on the skin surface and releases a bad smell called axillary osmidrosis. Objective: To evaluate the effect of power‐assisted rotary cutter with negative pressure suction through small incision for axillary osmidrosis. Methods: From January 2017 to January 2022, 647 patients with axillary osmidrosis underwent power‐assisted rotary cutter with negative pressure suction through small incision surgery to treat for axillary osmidrosis. The operation time (min), intraoperative bleeding (ml) and recovery time (days) were counted. Three months after operation, the amount of underarm sweat, the disappearance of underarm hair, the incidence of operation, the effective rate of operation, and the satisfaction of operation results were evaluated by questionnaire. Results: There were no postoperative complications except five cases of mild axillary pigmentation after 3 months. All patients evaluated good odor elimination. No patient was rated as average or poor. No recurrence. Conclusion: Power‐assisted rotary cutter with negative pressure suction through small incision is an effective and ideal surgical method to reduce the complications and recurrence of axillary osmidrosis.